Contemporary Trends and Age‐Specific Sex Differences in Management and Outcome for Patients With ST‐Segment Elevation Myocardial Infarction. Issue 12 (23rd November 2016) - De Luca, Leonardo; Marini, Marco; Gonzini, Lucio; Boccanelli, Alessandro; Casella, Gianni; Chiarella, Francesco; De Servi, Stefano; Di Chiara, Antonio; Di Pasquale, Giuseppe; Olivari, Zoran; Caretta, Giorgio; Lenatti, Laura; et al.
Abstract : Background: Age‐ and sex‐specific differences exist in the treatment and outcome of ST‐elevation myocardial infarction (STEMI). We sought to describe age‐ and sex‐matched contemporary trends of in‐hospital management and outcome of patients with STEMI. Methods and Results: We analyzed data from 5 Italian nationwide prospective registries, conducted between 2001 and 2014, including consecutive patients with STEMI. All the analyses were age‐ and sex‐matched, considering 4 age classes: <55, 55 to 64, 65 to 74, and ≥75 years. A total of 13 235 patients were classified as having STEMI (72.1% men and 27.9% women). A progressive shift from thrombolysis to primary percutaneous coronary intervention occurred over time, with a concomitant increase in overall reperfusion rates ( P for trend <0.0001), which was consistent across sex and age classes. The crude rates of in‐hospital death were 3.2% in men and 8.4% in women ( P <0.0001), with a significant increase over age classes for both sexes and a significant decrease over time for both sexes (all P for trend <0.01). On multivariable analysis, age (odds ratio 1.09, 95% CI 1.07–1.10, P <0.0001) and female sex (odds ratio 1.44, 95% CI 1.07–1.93, P =0.009) were found to be significantly associated with in‐hospital mortality after adjustment for other risk factors, but no significant interaction between these 2 variables was observed ( P for interaction=0.61). Conclusions: Despite a nationwide shift from thrombolytic therapy to primary percutaneous coronary intervention for STEMI affecting both sexes and all ages, women continue to experience higher in‐hospital mortality than men, irrespective of age.